COMPUTATION OF THE COHESIVE ENERGIES OF SOME SELECTED IONIC LIQUID CRYSTALS (NaCl AND LiCl) USING DENSITY FUNCTIONAL THEORY FHI-AIMS CODE (FUDMA JOURNAL OF SCIENCES, 2023)
The cohesive energies of lithium chloride (LiCl) and sodium chloride (NaCl) were computed using Density Functional Theory (DFT). DFT based Fritz Haber Institute-ab initio molecular simulation (FHI-aims) computer code has several input parameters in which some of the variables were optimized. The cohesive energies of LiCl and NaCl were calculated within Pardew Burke Ernzerhof (GGA), Perdew Wang and Pardew Zunger local density approximations (LDA) of DFT. The results obtained from the calculations of cohesive energies of LiCl and NaCl were approximately 4.8eV and 4.1eV respectively. These results obtained are in the neighborhood of experimentally found values of 4.86eV for LiCl and 4.26eV for NaCl within the reasonable percentage errors of 1.3% and 3.9% respectively. The major source of this deviation comes from the present DFT calculations of the ionic liquid rather than the atom. The result presented have also confirmed a faster and more accurate study of the ionic liquid considered when compared to literature report of other codes reporting higher iterations before convergence.
Keywords: Lattice constant, Ground state energy, Ionic liquid, GGA and LDA